(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The geography of tourism is a relatively recent idea, especially in relation to the term ofgeography, and it is characterized by complexity due to its linking of the two meanings of these words. Assuch, this study primary objective is to provide a comprehensive overview of cultural geography’sfunction and standing. Tourism. To stand out in the global tourism industry, culture is becoming anincreasingly vital component of the offering. Culture, tradition, manufacturing, and creativity can allbenefit financially from increased tourism, making it a crucial tool in preserving and fostering these keyaspects of society.